Boundary-spanning: reflections on the practices and principles of Global Health. Issue 1 (2nd June 2016) - Sheikh, Kabir; Schneider, Helen; Agyepong, Irene Akua; Lehmann, Uta; Gilson, Lucy
Abstract : As Global Health evolves, not merely as a metaphor for international collaboration, but as a distinct field of practice, it warrants greater consideration of how it is practiced, by whom, and for what goals. We believe that, to become more relevant for the health systems and communities that are their intended beneficiaries, Global Health practices must actively span and disrupt boundaries of geography, geopolitics and constituency, some of which are rooted in imbalances of power and resources. In this process, fostering cross-country learning networks and communities of practice, and building local and national institutions with a global outlook in low and middle-income countries, are critically important. Crucially, boundary-spanning practices in Global Health require a mindset of inclusiveness, awareness of and respect for different coexisting realities.